Exploring the Interactions Between Epidural Analgesia, Extubation and Reintubation Outcomes in Infants in Neonatal Care Units: A Retrospective Cohort Study - Mihaela Visoiu; Stephanie Parry; Tyler H. Augi; Danielle R. Lavage; Scott E. Licata; Holly A. Turula; Doreen E. Soliman (Children)
Background/Objectives: Continuous epidural analgesia is desirable for improving infant outcomes after surgeries. However, its contribution to facilitating extubation is not well known. Methods: A retrospective chart review was conducted at the UPMC Children’s Hospital of Pittsburgh to identify all infants who received an epidural catheter between 2018 and 2024 and required postsurgical admission to the Neonatal Intensive Care Unit (NICU). The study examined the timing of extubation and reintubation, along with associated factors, in 100 infants who underwent major surgeries. Results: In total, 100 infants, 43 females and 57 males, 40 (38.39–42.07) weeks corrected gestational age, 3 (2.52–3.42) kg received epidural catheters. Sixty-two patients had a pulmonary condition. Of 45 infants extubated in the operating room, 32 received fentanyl intraoperatively, and 16 required a morphine infusion in the NICU. Among 55 infants that remained intubated, 24% underwent a thoracic procedure, 46 received intraoperatively fentanyl, and 21 needed an opioid infusion postoperatively. The extubation day was median (IQR) 2 (1–4), and 24% remained intubated beyond day 5. Twelve infants were intubated preoperatively, and six required prolonged ventilation beyond day 5. Of 15 infants that required reintubation, 8 received a morphine infusion. The medians (IQR) of the average of three pain and sedation scores before reintubation were 1.67 (1–3) and 0 (−1.67–0), respectively. Conclusions: Epidural analgesia may facilitate early extubation in some infants undergoing surgeries. Morphine infusion was administered at a similar rate between infants extubated and those who remained intubated, and its role in delaying extubation timing remains unclear.